2016
DOI: 10.3906/sag-1507-18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the use of saline and seawater for nasal obstruction in children under 2 years of age with acute upper respiratory infection

Abstract: Relief was seen in nasal congestion, weakness, sleep quality, and nutrition with the use of both saline and seawater in children with the common cold. Seawater or saline drops may be added to standard treatment protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 21 publications
0
34
1
1
Order By: Relevance
“…A Cochrane review concludes that the evidence is very limited 12 . In a recent report, both NS and sea-water drops (thrice/day) reduced the severity of URTI symptoms in young children 13 .…”
Section: Introductionmentioning
confidence: 87%
“…A Cochrane review concludes that the evidence is very limited 12 . In a recent report, both NS and sea-water drops (thrice/day) reduced the severity of URTI symptoms in young children 13 .…”
Section: Introductionmentioning
confidence: 87%
“…There was no significant difference in the seawater and saline group; however, the children who received these interventions had significant relief in nasal congestion, sleep, and nutrition in comparison to placebo. [ 12 ]…”
Section: Resultsmentioning
confidence: 99%
“…Nasal saline drops reduced nasal congestion, weakness, rhinorrhea, and sleep quality in children <2 years who developed URTI. [ 12 ] Similarly, Wang et al . [ 13 ] found nasal saline wash benefited children with acute sinusitis in symptoms as assessed by the Pediatric Rhinoconjunctivitis Quality of Life Questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Nasal irrigation using normal saline (0.9%) and seawater spray (2.3%) were useful in preventing upper respiratory infections in children. 12 , 13 Saline water gargling and saline nasal irrigation at hypertonic concentrations (1.5-3%) showed protection against the common cold. 14 There is also evidence on the beneficial effect of saline irrigation in chronic inflammatory conditions like rhino-sinusitis 15 , 16 , which is characterized by the blockage of sinuses.…”
Section: Introductionmentioning
confidence: 97%
“…Disinfection of the irrigation vessel/pot is also vital because unclean vessels may enable lodging of particulate matter that may become a nidus for bacterial infection. However, these limitations are only speculative, and long-term studies have not shown the emergence of any such issues 10 , 11 , 12 , 13 , 14 . For some beginners, saline nasal irrigation may appear slightly difficult than gargling, but studies have shown this to be a well-tolerated approach 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%